Atomic jaya - Sulaiman, Huzir; Leow, Puay Tin *; Chee, Sek Thim * (Sunway University. Dept. of Performance & Media, 2008)
Brought together by a belacan-loving retired general, three physicists are holed up in a disused helicopter hangar working on Malaysia's very own and very first Atomic Bomb. Naturally this deadely mega project can only give rise to a string of absurd and hilarious situations that are unique to Malaysia, whether they be instances of shaky ethics, mispronunciations, misapprehensions, and outright non-comprehensions, cheerfully celebrated racism, denials in the media or just sheer incompetence. The people you meet in the play ar often genuinely quirky and even endearing.